Model checking software 18th International SPIN Workshop, Snowbird, UT, USA, July 14-15, 2011. Proceedings - Groce, Alex; Musuvathi, Madanlal (Lecture Notes in Computer Science, 2011)
This book constitutes the refereed proceedings of the 18th International SPIN workshop on Model Checking Software, SPIN 2011, held in Snowbird, UT, USA, in July 2011. The 10 revised full papers presented together with 2 tool demonstration papers and 1 invited contribution were carefully reviewed and selected from 29 submissions. The papers are organized in topical sections on abstractions and state-space reductions; search strategies; PROMELA encodings and extensions; and applications of model checking.